Turnierentlohnung im Versicherungsvertrieb - Steul-Fischer, Martina; Wedel, Michaela (Zeitschrift für die gesamte Versicherungswissenschaft, 2012)
For insurance companies, tournaments are one of the most important incentives to motivate and control insurance sales agents. We analyse the efficiency of tournaments for insurance sales agents and show that the level of prize and its exclusiveness, as well as the presentation of rank during the tournament, increase efficiency. © Springer-Verlag 2012.
WiSo-Import:2015-03-26:4164